2015
DOI: 10.3391/mbi.2015.6.4.08
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of suspected crayfish invasions in Missouri, U.S.A.: evidence for the prevalence of short-range translocations and support for expanded survey efforts

Abstract: Biological invasions are increasing in frequency and the need to mitigate or control their effects is a major challenge to natural resource managers. Failure to control invasive species has been attributed to inadequate policies, resources or scientific knowledge. Often, natural resource managers with limited funds are tasked with the development of an invasive species control program without access to key decision-support information such as whether or not an invasive species will cause damage, and what the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Research to date has found F. eupunctus primarily associated with higher order streams, greater groundwater spring flow volumes and higher current velocity, thus making F. eupunctus a large river habitat specialist relative to sympatric congeneric crayfishes (Flinders & Magoulick, ; Magoulick et al., ; Nolen et al., ). Faxonius eupunctus is recognised as Threatened by the American Fisheries Society (Taylor et al., ) and Vulnerable by the International Union for Conservation of Nature (Richman et al., ), and it is currently being evaluated for federal protection under the United States Endangered Species Act (ESA), owed in part to its narrowly endemic range and risk for displacement by non‐native crayfishes (DiStefano, Imhoff, Swedberg, & Boersig, ; Imhoff, Moore, & DiStefano, ). Given the rarity and conservation need of this organism, eDNA may prove useful in better defining the distribution of F. eupunctus within the Eleven Point River drainage, including evaluating the species’ potential use of tributary streams.…”
Section: Introductionmentioning
confidence: 99%
“…Research to date has found F. eupunctus primarily associated with higher order streams, greater groundwater spring flow volumes and higher current velocity, thus making F. eupunctus a large river habitat specialist relative to sympatric congeneric crayfishes (Flinders & Magoulick, ; Magoulick et al., ; Nolen et al., ). Faxonius eupunctus is recognised as Threatened by the American Fisheries Society (Taylor et al., ) and Vulnerable by the International Union for Conservation of Nature (Richman et al., ), and it is currently being evaluated for federal protection under the United States Endangered Species Act (ESA), owed in part to its narrowly endemic range and risk for displacement by non‐native crayfishes (DiStefano, Imhoff, Swedberg, & Boersig, ; Imhoff, Moore, & DiStefano, ). Given the rarity and conservation need of this organism, eDNA may prove useful in better defining the distribution of F. eupunctus within the Eleven Point River drainage, including evaluating the species’ potential use of tributary streams.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental variables, such as temperature and flow, can influence range expansion and competitive abilities of invading crayfishes, which may lead to the exclusion of na-tive species (Flynn and Hobbs 1984, Bubb et al 2004, Mazlum and Eversole 2005. For example, future populations of the narrowly endemic Spothand Crayfish could be affected by the introduced Virile Crayfish Faxonius virilis (Hagen, 1870), which has invaded at least 117 km of the Current River downstream of JFR study sites (DiStefano et al 2015, Rozansky 2019. Virile and Spothand crayfishes are ecologically (Pflieger 1996), morphologically (Rozansky 2019), and genetically (Crandall andFitzpatrick 1996, Taylor andKnouft 2006) similar.…”
Section: Temperature-maxima Responsesmentioning
confidence: 99%
“…Biologists have documented crayfi sh invasions at more than 31 locations in Missouri, and statewide mail surveys of Missouri bait and pet stores in 2010 indicated that both industries could be prominent crayfi sh introduction pathways (DiStefano et al 2015(DiStefano et al , 2016. The Missouri Department of Conservation (MDC) implemented regulations in 2014 to reduce introductions by limiting sales of crayfi sh in bait and pet stores to one native species, the virile crayfi sh Faxonius virilis , and provided associated educational materials to all bait stores (DiStefano et al 2015(DiStefano et al , 2016. Despite MDC ' s focus on the bait industry, prior to the current study, the agency had not examined pet stores as pathways for potentially invasive crayfi sh or compliance with the 2014 regulation.…”
Section: Introductionmentioning
confidence: 99%